2022
DOI: 10.3390/languages7010060
|View full text |Cite
|
Sign up to set email alerts
|

Can Heritage Speakers Predict Lexical and Morphosyntactic Information in Reading?

Abstract: Ample evidence suggests that monolingual adults can successfully generate lexical and morphosyntactic predictions in reading and that correct predictions facilitate sentence comprehension. In this eye-tracking corpus reading study, we investigate whether the same is true for reading in heritage language. Specifically, we ask whether heritage speakers (HSs) of Russian are able to anticipate lexical and/or morphosyntactic information of the upcoming words in the sentence and whether they differ in the prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…As for language use effects, we anticipate that greater language use will produce more fixations to target verbs. This is in line with studies showing that greater language use facilitates morphosyntactic processing (L2 learners: Faretta-Stutenberg and Morgan-Short, 2018 ; HSs: Foote, 2011 ; Caffarra et al, 2017 ; Keating, 2022 ) and prediction (HSs: Parshina et al, 2022 ), as well as L2 sound discrimination ( Flege and MacKay, 2004 ; Black et al, 2020 ), monolingual-like pronunciation in HSs ( Lloyd-Smith et al, 2019 ), and reduced L2 accent ( Guion et al, 2000 ). Lastly, we postulate that language use will have a stronger impact on prediction than language proficiency in both HSs and L2 learners, but particularly in the HSs.…”
Section: The Studysupporting
confidence: 91%
See 2 more Smart Citations
“…As for language use effects, we anticipate that greater language use will produce more fixations to target verbs. This is in line with studies showing that greater language use facilitates morphosyntactic processing (L2 learners: Faretta-Stutenberg and Morgan-Short, 2018 ; HSs: Foote, 2011 ; Caffarra et al, 2017 ; Keating, 2022 ) and prediction (HSs: Parshina et al, 2022 ), as well as L2 sound discrimination ( Flege and MacKay, 2004 ; Black et al, 2020 ), monolingual-like pronunciation in HSs ( Lloyd-Smith et al, 2019 ), and reduced L2 accent ( Guion et al, 2000 ). Lastly, we postulate that language use will have a stronger impact on prediction than language proficiency in both HSs and L2 learners, but particularly in the HSs.…”
Section: The Studysupporting
confidence: 91%
“…Four online HS studies did not measure language use, but their findings appeared to be attributable to language use and exposure. These HS studies employed written tasks, using self-paced reading ( Foote, 2011 ), eye-tracking ( Keating, 2022 ; Parshina et al, 2022 ), and ERPs ( Caffarra et al, 2017 ). In Foote, HSs and bilingual native speakers raised abroad were equally sensitive to gender and number agreement violations.…”
Section: The Role Of Aoo Proficiency and Use On Bilingual Language Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency was calculated from the sub-corpus of texts for children of the years 1920-2015 of the Russian National Corpus. For all words in the sentences, we collected predictability data in an online cumulative cloze task with 46 children (24 girls, M=11.3, range 9-12) who did not participate in the eye-tracking study (for details see Parshina et al, 2022b). Predictability was measured as the number of correct guesses divided by the total number of guesses.…”
Section: Methodsmentioning
confidence: 99%
“…In a study that employed eyetracking with written stimulus sentences rather than auditory stimuli, Keating (2022) compared the processing of Spanish gender agreement among heritage speakers who had acquired their two languages simultaneously to those who had acquired them sequentially and found that online sensitivity occurred earlier in the eye movement record for the sequential bilinguals, who had longer exposure to just Spanish before beginning to acquire the majority language, English. Parshina et al (2022) also used eyetracking with text to show that heritage speakers of Russian could predict lexical and morphosyntactic information for upcoming words while reading and that this ability appeared to correlate with literacy experience in Russian. Lastly, Parshina et al (2021) used eyetracking to document some general tendencies in the reading behavior of heritage speakers of Russian as compared to monolingual readers, more specifically, that they read more slowly, that they were less likely to skip words (which is a normal part of fluent reading), and that they were more likely to reread than the comparison group.…”
Section: Literature Reviewmentioning
confidence: 99%